Genetic studies facilitated management decisions on the invasion of the ruddy duck in Europe - Muñoz-Fuentes, Violeta; Green, Andy J.; Negro, Juan J. (Biological Invasions, 2013)
The ruddy duck (Oxyura jamaicensis), a stifftail native to the Americas, was introduced to the UK in the 1950s and has since been recorded in 22 western Palearctic countries. By 2000, the UK popu- lation peaked at nearly 6,000 individuals. In 1991, hybridisation with the native and globally threatened (IUCN Endangered) white-headed duck (Oxyura leu- cocephala), a stifftail restricted to the Mediterranean and Asia, was recorded in Spain and culling of hybrids and ruddy ducks began. Here we report on a series of genetic studies that have enabled and supported management decisions to the benefit of the white- headed duck. First, genetic data confirmed that these are two distinct species, each of which is more closely related to other stifftail species. Second, molecular studies indicated that ruddy ducks in Spain, Iceland and elsewhere in Europe were of captive origin and not descendants from vagrants from their native North America. Third, genetic methods were used to distin- guish among different hybrid generations in Spain and detected no ruddy duck introgression in birds identi- fied morphologically as white-headed ducks. Collec- tively, these results supported management decisions to eradicate ruddy ducks from Europe. Subsequently, a control programme reduced the UK population by over 95 % by 2010, and the arrival of ruddy ducks to Spain decreased from 21 birds in 2003 to two sightings in 2010–2011. However, increased efforts to control small ruddy duck populations elsewhere in Europe and Morocco are still required to ensure conservation of the white-headed duck. This case of invasion by hybridization demonstrates that successful control is feasible given early detection followed by a rapid response plan; it also shows the contribution of research to management and that to guarantee the conservation of an endangered native species action may be required in countries outside its distribution range. Peer reviewed